DINAMIKA PENGGUNAAN KATA DAN ISTILAH DALAM KARYA SASTRA INDONESIA DAN IMPLIKATURNYA - Abdul Manaf, Ngusman (Humanus, 2015)
The purpose of the article is (1) to gather empirical facts about the use of words and terms in Indonesian literatures, (2) understand implicature (aditional message) behind the the dynamic use of words and terms in Indonesian literatures. The fact about awareness of the usage of Indonesian language in literatures is expected to be supporting data in the development of Indonesian language history. The source of the data is Indonesian literatures including novels. The data are collected by reading technique, marking out, and taking notes. The data are analyzed using comparison technique, a technique that use words or terms in certain time and compared to those from another time. The result of this analysis shows that in 1980’s, many Indonesia literatures used vernacular words and terms. This period of time can be used as an alternatif to mark the development of Indonesian language, especially the development of the vocabulary. Besides, the use of words and terms in the speech of Indonesian novel characters are an implication that Indonesian society, particularly the writers are worried that traditional culture will be shifted by national culture. They want to be Indonesians without losing their traditional culture.Keywords: implicature, dinamyc use of words and terms, Indonesian, literature